2012
DOI: 10.1111/cup.12022
|View full text |Cite
|
Sign up to set email alerts
|

Epidermotropic secondary cutaneous involvement by relapsed angioimmunoblastic T‐cell lymphoma mimicking mycosis fungoides: a case report

Abstract: Angioimmunoblastic T-cell lymphoma (AITL) is frequently associated with skin lesions, but epidermotropic cutaneous involvement has never been described. A 37-year-old man presented with erythematous and pruriginous plaques, clinically suggestive of mycosis fungoides, distributed all over the body, 3 weeks after the last line of a polychemotherapy, given for an AITL diagnosed 1 year earlier on a lymph node biopsy. Skin biopsy showed an epidermotropic CD4(+) T-cell lymphoma, so that a diagnosis of mycosis fungo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…PTCL-NOS or angioimmunoblastic T-cell lymphoma (AITL). 8 Of note, systemic involvement has not been showed in any of the reported patients with CT FH CL. As nodal T FH lymphomas also express PD-1, ICOS, CXCL13 and potentially CD10 and bcl6, 3 a complete staging must be performed in any case of cutaneous lymphoma manifestations to exclude cutaneous spread of systemic lymphoma.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…PTCL-NOS or angioimmunoblastic T-cell lymphoma (AITL). 8 Of note, systemic involvement has not been showed in any of the reported patients with CT FH CL. As nodal T FH lymphomas also express PD-1, ICOS, CXCL13 and potentially CD10 and bcl6, 3 a complete staging must be performed in any case of cutaneous lymphoma manifestations to exclude cutaneous spread of systemic lymphoma.…”
Section: Discussionmentioning
confidence: 79%
“…Important differential diagnoses in cases with or without epidermotropic T‐helper cell phenotype are secondary cutaneous manifestations of nodal peripheral T‐cell lymphomas, e.g. PTCL‐NOS or angioimmunoblastic T‐cell lymphoma (AITL) . Of note, systemic involvement has not been showed in any of the reported patients with CT FH CL.…”
Section: Discussionmentioning
confidence: 97%
“…Both follicular dendritic cell hyperplasia and the presence of high endothelial venules are highly characteristic of lymph node specimens infiltrated by AITL . Nevertheless, none of the authors have reported expansion of follicular dendritic cells meshwork on skin specimens infiltrated by AITL . Moreover, capillary hyperplasia is not always present on skin specimens and its presence lacks diagnostic specificity because it could be found in many other conditions .…”
Section: Discussionmentioning
confidence: 98%
“…Within the large group of PTCL‐NOS, it is also recognized, that a subset has TFH‐like features, in the form of its specific molecular profile, a similar genetic signature and/or show overlapping pathologic features . The frequency of skin involvement in the setting of AITL varies according to the series, ranging from 2 to 50% of the patients . The histopathologic spectrum of secondary cutaneous involvement by AITL is very broad.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal populations of T-cells are seen in 87% of cases and clonal B-cells can be found in up to 40–80% of cases (with only 5 cases tested from previous reports) 10,39 . Uncommon histologic presentations include granulomatous dermatitides 4,40 , an atypical linear IgA dermatosis form 40 , prurigo-like eruptions 41 , and rarely an epidermotropic form mimicking mycosis fungoides (MF) 42 .…”
Section: Discussionmentioning
confidence: 99%